Water and Wastewater Services in the Danube Region : Serbia Country Note - World Bank (Washington, DC, 2015)
To evaluate the sustainability of services in the region, an overall sector assessment has been done taking into account four main dimensions: access to services, quality of services, efficiency of services, and financing of services. Each of these dimensions is measured through three simple and objective indicators. For each indicator, best practice values are established by looking at the best performers in the region, and the countries closest to those best performers are deemed to have a more mature sector. A more complete description of the methodology to assess sector sustainability is included in the annex of the state of the sector regional report from the Danube Water Program. The outcomes of this assessment for the Serbian water sector are presented, which also shows average and best practices in the Danube region. The Serbian sector sustainability score is 61, which is below the Danube average sustainability of 64. The assessment shows that, on average, the country performs well in terms of access to piped water and flush toilets, nonrevenue water, and affordability. The main deficiencies of the Serbian water sector identified through the sector sustainability assessment are the level of investment, wastewater treatment coverage, and the operating cost ratio. The main sector challenges are: strengthening and clarifying sector governance; ensuring tariff setting according to the cost recovery principle to improve overall performance in preparation for EU accession; and enhancing water utility staff capacity and training.